Innovative smart healthcare and bio-medical systems AI, intelligent computing and connected technologies - Salem, Abdel-Badeeh M. (Boca Raton : CRC Press, 2020)
Advances in smart healthcare systems (SHS) and artificial intelligence (AI) domains highlight the need for ICT systems that aim not only to improve human quality of life but improve safety too. SHS bring together concepts and methodologies from various fields, such as communications and network systems, computer science, life sciences and healthcare. The well-known smart healthcare paradigms are; real-time monitoring devices, computer-aided surgery devices, telemedicine devices, population-based care devices, personalized medicine from a machine learning perspective, ubiquities intelligent computing, expert decision support systems, Health 2.0 and Internet of Things (IoT). This book presents models for the deployment of intelligent computing, information, and networking technologies to aid in preventing disease, improving the quality of care and lowering overall cost. It also discusses the potential role of the AI paradigms, computational intelligence and machine learning techniques which are used in developing the SHS. It will provide examples of potential usage of such technology in smart healthcare and and bio-medical systems. It will be an important read for researchers and professionals working in smart healthcare systems, as well as those working in the individual areas of networks, artificial intelligence and healthcare who want to see how an interdisciplinary approach can enhance the current technology.
OCLC-licensed vendor bibliographic record.
Keywords: Medical care -- Technological innovations; Medical technology; Biomedical engineering; Artificial intelligence -- Medical applications; COMPUTERS / Artificial Intelligence; MEDICAL / Health Care Delivery